Caracterização magnética do compósito multiferróico (1-x)Pb(Mg1/3Nb2/3)-xPbTiO3/NiFe2O4 - Gualdi, Alexandre José (Universidade Federal de São Carlos, 2010)
In this work we studied the magnetic properties of nickel ferrite and the (1-x)Pb(Mg1/3Nb2/3)-xPbTiO3/NiFe2O4 (PMN-PT/NFO) multifferroic composite syntherized in different temperatures. The magnetization, magnetostriction and magnetoelectric effect measurements were performed as a function of applied magnetic field at room temperature. The goals of the work were the developement of the instrumentation. For magnetoestriction measurements a capacitive cell was design for this application. The magnetoelectric measurements were performed in two experimental setup: one uses the Physical Properties Measurements System (PPMS) by Quantum Design and the other system was adapted in a vibration sample magnetometer (VSM) We observed that magnetic properties present a dependence with the synthesis conditions as well as the nickel ferrite than the composite sample. We observed also an intrinsic dependence with the magnetostriction properties of composite.
Keywords: Magnetismo; Magnetoestricção; Magnetoelétrico; Célula capacitiva; CIENCIAS EXATAS E DA TERRA::FISICA